Human nasal olfactory stem cells, purified as advanced therapy medicinal products, improve neuronal differentiation - Jaloux, Charlotte; Bonnet, Maxime; Vogtensperger, Marie; Witters, Marie; Veran, Julie; Giraudo, Laurent; Sabatier, Florence; Michel, Justin; Legré, Regis; Guiraudie-Capraz, Gaëlle; Féron, François (Frontiers in Neuroscience, 2022)
Background: Olfactory ecto-mesenchymal stem cells (OE-MSC) are mesenchymal stem cells derived from the lamina propria of the nasal mucosa. They display neurogenic and immunomodulatory properties and were shown to induce recovery in animal models of spinal cord trauma, hearing loss, Parkinsons’s disease, amnesia, and peripheral nerve injury. As a step towards clinical practice, we sought to i) devise a culture protocol that meets the requirements set by human health agencies and ii) assess the efficacy of stem cells on neuron differentiation. Methods: Nasal olfactory mucosa biopsies from three donors were used to design and validate the good manufacturing process for purifying stem cells. All processes and procedures were performed by expert staff from the cell therapy laboratory of the public hospital of Marseille (AP-HM), according to aseptic handling manipulations. Premises, materials and air were kept clean at all times to avoid cross-contamination, accidents, or even fatalities. Purified stem cells were cultivated for 24 or 48 hours and conditioned media were collected before being added to the culture medium of the neuroblastoma cell line Neuro2a. Results: Compared to the explant culture-based protocol, enzymatic digestion provides higher cell numbers more rapidly and is less prone to contamination. The use of platelet lysate in place of fetal calf serum is effective in promoting higher cell proliferation (the percentage of CFU-F progenitors is 15,5%), with the optimal percentage of platelet lysate being 10%. Cultured OE-MSCs do not show chromosomal rearrangement and, as expected, express the usual phenotypic markers of mesenchymal stem cells. When incorporated in standard culture medium, the conditioned medium of purified OE-MSCs promotes cell differentiation of Neuro2a neuroblastoma cells. Conclusions: We developed a safer and more efficient manufacturing process for clinical grade olfactory stem cells. With this protocol, human OE-MSCs will soon be used in a Phase I clinical based on their autologous transplantation in digital nerves with a neglected injury. However, further studies are required to unveil the underlying mechanisms of action.